Stakeholder legitimacy and efficiency: the case of innovation at the Port of Tema, Ghana - Acheampong, G.; Aryee, J.; Andersen, T.; Hansen, A.S. (International Journal of Business and Globalisation, 2022)
Our study set out to explore the relationship between legitimacy in the form of social license that stakeholders grant the National Single Window Project (NSWP) and port efficiency at the Port of Tema, as well as bounding conditions on this relationship. We collected stakeholder legitimacy data in line with with the social license to operate (SLO) framework on the National Single Window Project implementation at the port and stakeholder-perceived port efficiency in Tema. We found that there is an ׈-shaped relationship between legitimacy and port efficiency. We also found that port cooperation and relational intensity dampens the relationship between legitimacy and portability. efficiency. Our study offers an alternative perspective on port management that view ports as isolated units, which provides a partial understanding of their functioning. We opine that viewing ports as networks of stakeholders provides an improved understanding.
Research Article
Keywords: port efficiency; legitimacy; social license